The Practical Value of Traditionboweron Javanese Traditional Weddings: A Study in D. Tegalrejo Village, Tugumulyo District, Musi Rawas Regency, South Sumatra - Susanto, Susanto; Iswatiningsih, Daroe (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study examines the transformation of the munjung tradition in Javanese wedding ceremonies within the transmigrant community of Tegalrejo Village, Musi Rawas, South Sumatra. Munjung, a form of respect and invitation through the delivery of food, has undergone changes in form and meaning due to evolving times, economic conditions, and the impact of the pandemic. This research adopts a qualitative approach with an intrinsic case study design. Data were collected through semi-structured interviews, participant observation, and documentation, with informants selected using purposive and snowball sampling techniques. Analysis based on the Miles and Huberman model revealed three key themes: changes in the containers and contents of punjungan, rationalization of practicality, and the persistence of symbolic values in an adaptive form. Despite physical transformations, the social and cultural functions of munjung persist as symbols of respect and social bonding. This study enriches the understanding of cultural adaptation among migrant communities and emphasizes the importance of preserving local traditions in a contextualized manner. The implications include strengthening character education based on local culture, informing policies on cultural preservation, and providing direction for future research on symbolic and ecological aspects.